Fractionated small cell‐free DNA increases possibility to detect cancer‐related gene mutations in advanced colorectal cancer. Issue 5 (27th June 2020) - Ishida, Yasuaki; Takano, Shinichi; Maekawa, Shinya; Yamaguchi, Tatsuya; Yoshida, Takashi; Kobayashi, Shoji; Iwamoto, Fumihiko; Kuno, Toru; Hayakawa, Hiroshi; Matsuda, Shuya; Fukasawa, Mitsuharu; Shindo, Hiroko; et al.
Abstract: Background and Aim: Liquid biopsy is a method that can efficiently detect tumor genetic abnormalities from body fluids such as blood and urine. Detection sensitivity and the available number of mutations in cell‐free DNA (cfDNA) are limited. In this study, we develop a highly sensitive and comprehensive method to detect mutations from cfDNA by concentrating tumor fractions of small cfDNA in advanced colorectal cancers. Methods: Biopsied specimens and 37 serum samples were collected from 27 patients with advanced colorectal carcinoma. A serum‐extracted cfDNA was divided into enriched fractionated small cfDNA and unfractionated cfDNA. Both cfDNAs were subjected to digital polymerase chain reaction (PCR) to evaluate their KRAS, BRAF, CDKN2A, and TP53 status. Consequently, their mutant allele frequencies (MAFs) were compared and analyzed by next‐generation sequencing (NGS) in conjunction with tissue‐derived DNA. Results: NGS analyses revealed mutations in TP53 (63%), KRAS (63%), APC (30%), and PIK3CA (22%). Digital PCR could detect mutations in 25 of 27 samples (93%) of unfractionated cfDNA, a rate that increased to 100% when samples were enriched with fractionated small cfDNA (6.8 vs 10.7%, P < 0.001). NGS also showed increased MAFs in fractionated small cfDNA compared to unfractionated cfDNA (16.3 vs 18.8%, P = 0.012) and a tendency to detect a greater number of cancer‐related genes in fractionated cfDNA. Conclusions: Fractionated small cfDNA increased MAFs of gene mutations and increases the possibilities to detect cancer‐related genes even in advanced cancer patients from whom it is difficult to obtain tissue samples. Abstract : In this study, we develop a highly sensitive and comprehensive method to detect mutations from cell‐free DNA (cfDNA) by concentrating tumor fractions of small cfDNA in advanced colorectal cancers. Fractionated small cfDNA increased mutant allele frequencies of gene mutations and increases the possibilities to detect cancer‐related genes even in advanced cancer patients from whom it is difficult to obtain tissue samples.